Gastric Schwannoma: Discussion of a clinical case - Cabillón, José; Estapé Viana, Gonzalo; Santiago, Pablo; Gualco, G; Ardao, G (Cirugía del Uruguay, 2006)
A female patient had a mesenchymal gastric tumor. After prior paraclinical evaluation for the purpose of establishing diagnosis, it was resected. Conventional anatomopathology showed a histological pattern compatible with that of a gastrointestinal stromal tumor (GIST). Immunohistochemical compulsory confirmation showed: CD117 and CD34 – together with S-100 +, confirming the gastric schwannoma diagnosis. The paper then describes the clinical case highlighting those aspects considered worthwhile